Keaktifan Aplikasi Emis Dilembaga Keagamaan dan Pontren di Kantor Kementrian Agama Kota Sawahlunto - Elizasri, Elizasri; Hendriani, Suswati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This study aims to answer the research focus on (1) Management of the Education Management Information System (EMIS) at Religious Institutions and Islamic Boarding Schools in the office of the Ministry of Religion in Sawalunto City (2) Administrative Services and Human Resources at Diniyah Education Institutions and Islamic Boarding School of the Ministry of Religion of Sawalunto City (3) utilization of the Education Management Information System (EMIS) in improving administrative services and human resources at Diniyah Education institutions and Islamic Boarding Schools of the Ministry of Religion of Sawalunto City.This study used a qualitative-descriptive approach and used data collection techniques. Data collection methods were obtained using in-depth interviews, field observations, and documentation. Data analysis techniques use data reduction (data reaction), data presentation (data display), and conclusion drawing and verification. So this study obtained results based on data exposure, and findings and discussion analysis, based on the results of this study it can be described as follows: an education management information system already exists and is implemented, evidenced by the existence of a school website application that existed at the time of the study.